Assisted-freehand ultrasound elasticity imaging. - Kadour, M; Noble, J (2009)
Good-quality elasticity imaging requires highly controlled compressions of the breast, which are often challenging to obtain with freehand, even by an experienced radiologist. This paper presents assisted-freehand ultrasound (AFUSON): a fusion of freehand and automated ultrasound systems designed to assisted elasticity imaging acquisition while remaining as flexible as freehand. In the form of a hand-held device, this semi-automatic solution delivers both increased acquisition precision and control. Compared with freehand acquisitions, it reduces out-of-plane motion decorrelation by one-half and lateral motion by one-third, increases within-scan repeatability by 50%, and does so across operators.